On the fracture process zone near the front of an arbitrary crack in a solid - Bogdanova, O.S.; Kaminsky, A.A.; Kurchakov, E.E. (Reports of the National Academy of Sciences of Ukraine, 2017)
The model of the fracture process zone near the front of an arbitrary crack in a solid is proposed. Within the framework of this model, the constitutive equations relating the contravariant components of a stress vector with the covariant components of a displacement vector are derived. The local fracture criterion is formulated.